2021
DOI: 10.3389/fpls.2021.683690
|View full text |Cite
|
Sign up to set email alerts
|

Improving Plant Health Through Nutrient Remineralization in Aquaponic Systems

Abstract: The exploitation of readily bioavailable fish excreta as a source of plant nutrients lies at the cornerstone of aquaponics farming. Research on nutrient cycling in aquaponic systems has devoted considerable attention to the plant uptake of dissolved nutrients in fish excreta, however, the integration of particulate-bound nutrients into downstream hydroponic farming has remained elusive. The high amount of organic carbon present in fish sludge may lead to biofouling if directly incorporated into hydroponic circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…Future studies must likewise determine whether aquaponic facilities benefit from sterilization, or whether the co-cultivation of plants and fish in an environment promoting diversity leads to a more resilient facility-wide microbiome. Secondly, in line with previous work on the relationship between aqueous nutrient concentrations and plant health ( Lobanov et al, 2021 ), more research is needed to determine whether a greater focus on maintaining plant health as opposed to only maximizing yield will lead to more disease-tolerant crops, and ultimately more productive crops.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Future studies must likewise determine whether aquaponic facilities benefit from sterilization, or whether the co-cultivation of plants and fish in an environment promoting diversity leads to a more resilient facility-wide microbiome. Secondly, in line with previous work on the relationship between aqueous nutrient concentrations and plant health ( Lobanov et al, 2021 ), more research is needed to determine whether a greater focus on maintaining plant health as opposed to only maximizing yield will lead to more disease-tolerant crops, and ultimately more productive crops.…”
Section: Discussionmentioning
confidence: 93%
“…The above trends indicate community consolidation in our system, suggesting that prioritizing plant health metrics will likewise reduce the potential for disease. We have recently demonstrated that trace nutrients are not taken up by plants proportionally to their external aqueous concentrations ( Lobanov et al, 2021 ), which suggests that fundamental issues such as plant nutritional needs should be prioritized. Given the slow growth requirements of k-strategists [e.g., anammox ( Laureni et al, 2015 ; Zhang et al, 2017 ; Zielińska et al, 2018 ), archaea ( Seyler et al, 2014 ; Bartelme et al, 2017 )], system-wide maturation of the microbial population may take months or years ( Savidov and Brooks, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity of the forms of ammonia (NH 3 ) increases with water pH (the ammonia/ammonium ratio increases at pH 7 and above), which is one of the reasons for the importance of pH control in aquaculture. Aquaculture systems including autotroph biofloc technology (ABFT) [19], biofloc technology (BFT) [70], recirculating aquaculture systems (RAS) [71], and integrated multi-trophic aquaculture (IMTA) [72] systems such as aquaponic systems [73], constructed wetlands [74], integrated marine systems [75], high-rate algal ponds [76], periphyton systems [77], and partitioned aquaculture systems [78] aim mainly to remove nitrite-N (NO 2 -N) and ammonia (NH 3 ). Therefore, the four strains used in this study can be utilized in aquaculture, as they were shown to be excellent in their water-quality-improvement utilities.…”
Section: Practical Applications and Future Research Prospectsmentioning
confidence: 99%
“…With the current state-of-the-art, only the dissolved nutrients from the process water are being used for plant cultivation; however, some nutrients are often lacking in this solution [14]. Further, if directly transferred into the hydroponics system, the significant amount of organic carbon inside the solids may lead to biofouling, clogging, and undesired oxygen depletion in the system [15].…”
Section: Introductionmentioning
confidence: 99%